STUDENT CORNER LEARNING CONSTRUCTION AT MTS-MA AL-QUR'AN LA RAIBA HANIFIDA JOMBANG - Rizal, Ahmad Saiful; Syaifulloh, Ahmad (Journal of Industrial Engineering & Management Research, 2021)
The role of the teacher as an educator began to shift to become a facilitator or tutor. Students are given the opportunity to discuss the teaching materials they have learned. This method makes students understand the teaching material better than if it is explained directly through the teacher's lecture. This is then applied to the student learning activities of MTs-MA al-Qur'an La Raiba Hanifida which are not found in any school in the world. Although this learning activity is still classified as a new learning model, the theoretical basis that constructs this activity is quite strong and scientific. No wonder the principal and the head of the foundation still maintain this activity as one of the leading activities that will continue to be evaluated and improved from time to time. This learning activity is called the Student Corner. Therefore, the researcher was inspired to conduct research to explain how the Student Corner Learning Model, Activities and develop student learning corners at MTs-MA al-Qur'an La Raiba Hanifida Jombang. The research method used in this study is a qualitative method with a multi-site study design.This study obtained the results, namely First, it can simply be concluded that the learning model applied to the Student Corner is the implementation of Active Learning. However, Active Learning has not been able to represent the so-called Student Corner. Because basically Student Corner is just the name of a learning program that has been modified by MTs-MA al-Qur'an La Raiba Hanifida. While Active Learning is a name for learning theory. Second, the Student Corner learning activities include; a) students' creativity which is continuously stimulated every day through the making of Mind Mapping. b) students are trained in delivering the subject matter. 3) students' self-confidence increased dramatically after being trained regularly in each presentation. Third, Student Corner learning activities are constructed from three theories; Constructivist, Cognitivistic and Mind Mapping. Constructivistic theory teaches students how to build knowledge independently. Then Cognitivistic theory teaches the importance of a learning process rather than results. While the Mind Mapping theory teaches students to think creatively and makes it easier for students to absorb information in a creative note.